Characterization of absorbing aerosol types using ground and satellites based observations over an urban environment. (February 2017) - Bibi, Samina; Alam, Khan; Chishtie, Farrukh; Bibi, Humera
Abstract: In this paper, for the first time, an effort has been made to seasonally characterize the absorbing aerosols into different types using ground and satellite based observations. For this purpose, optical properties of aerosol retrieved from AErosol RObotic NETwork (AERONET) and Ozone Monitoring Instrument (OMI) were utilized over Karachi for the period 2012 to 2014. Firstly, OMI AODabs was validated with AERONET AODabs and found to have a high degree of correlation. Then, based on this validation, characterization was conducted by analyzing aerosol Fine Mode Fraction (FMF), Angstrom Exponent (AE), Absorption Angstrom Exponent (AAE), Single Scattering Albedo (SSA) and Aerosol Index (AI) and their mutual correlation, to identify the absorbing aerosol types and also to examine the variability in seasonal distribution. The absorbing aerosols were characterized into Mostly Black Carbon (BC), Mostly Dust and Mixed BC & Dust. The results revealed that Mostly BC aerosols contributed dominantly during winter and postmonsoon whereas, Mostly Dust were dominant during summer and premonsoon. These types of absorbing aerosol were also confirmed with MODerate resolution Imaging Spectroradiometer (MODIS) and Cloud-Aerosol Lidar and Infrared Pathfinder Satellite Observation (CALIPSO) observations. Highlights: For the first time absorbing aerosols have been characterized in the region. Characterizing techniques discriminates three major absorbing aerosol types. During summer and pre-monsoon, Mostly Dust aerosols were dominant. During winter and post-monsoon, Mostly BC aerosols were dominant. Aerosol types discriminated from AERONET were in good agreement with MODIS & CALIPSO.